Pola Komunikasi Orang Tua Tunggal dalam Berinteraksi dengan Anak di Medan Tembung - Sapriannnur, Annisa; Putri Aulia, Mega; Sazali, Hasan; Andinata, Maulana (IAIN Madura, 2023)
This study aims to analyze the communication patterns used by single parents in interacting with children in the city of Medan Tembung. Single parents are individuals who play a dual role as parents and at the same time earn the sole breadwinner in the family. This study involved a number of single parents in the Medan Tembung City area and analyzed the communication patterns they use in their daily interactions with their children.This study uses qualitative methods with data collection techniques through in-depth interviews and participatory observation. The results of this study found several challenges faced by single parents in interacting with children, such as time constraints, physical and emotional fatigue, and differences in needs and expectations between parents and children. Despite this, single parents still try to maintain good communication with their children.In conclusion, this study provides an overview of the communication patterns of single parents in interacting with children in the city of Medan Tembung. The results of this study can provide a better understanding of the dynamics of communication in single-parent families, and are expected to contribute to the development of more effective communication strategies and support positive relationships between single parents and children. In addition, this research will also found differences in communication patterns between single parents who are separated and single parents who are separated by death.